Analysis Of Patient Satisfaction With Pharmacy Services At Sail Health Center, Pekanbaru - Novia Sinata; Cindy Oktaviana Laia; Elsha Fadhika Dwi Ramadhani; Leni Marlina; Lisa Andriyani Siregar; Nadira Atiqah Ricardo (Excellent Health Journal, 2025)
Patient satisfaction issues with pharmaceutical installations can vary, including service quality, communication, waiting time, and other factors related to pharmaceutical services. Factors such as reliability, responsiveness, empathy, assurance, and physical evidence greatly influence patient satisfaction. This study aims to describe the level of patient satisfaction with the services provided at the Sail Pekanbaru Health Center Pharmacy Installation. Data were collected through questionnaires given to 50 patients who came for treatment and met the inclusion criteria in the period 28 October - 1 November 2024. The questionnaire was compiled based on the modified SERVQUAL method, with five variables, namely reliability, responsiveness, empathy, assurance, and tangible. Each variable consists of 4 questions. The results of sociodemographic data show that the majority of respondents are aged 17–40 years (52%), female (74%), have secondary education (56%), and work in the informal sector or are unemployed (42%). The results showed that in all dimensions, most respondents were satisfied with the services provided. The highest average level of satisfaction was in the tangible dimension with 42.5% of respondents stating very satisfied, and the lowest in the responsiveness dimension with 26% of respondents stating very satisfied. Although there were some notes on the aspects of supporting facilities and the comfort of the waiting room, in general patients stated that they were satisfied with the pharmaceutical services at the Sail Health Center.